2021
DOI: 10.1177/0022057420988703
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Medicinal Plants and Practices in Cagraray Island: Resources for Culture-Based Lessons in Biology

Abstract: The study aimed to develop culture-based lessons in Biology 9, integrating indigenous medicinal plants and practices in Cagraray Island. These developed lessons were designed incorporating features of research results, problem-based approach, active learning, and culture- or context-based teaching. The accounts from eight folk healers revealed the abundance of indigenous medicinal plants and practices for treating wounds, hypertension, anemia, cough and colds, and asthma. These illnesses were used as springboa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Expanding upon the records of literature, attempts have been made to improve science teaching strategies and academic achievement of learners. Many proposals were integrated into school curriculum like adaptation of constructivist view of learning (Garbett, 2011), integration of inquiry-based approach for teaching (Abdi, 2014), ICT integration (Palomares-Ruiz et al, 2020), contextualization or culturebased instruction (Bibon, 2021), and brain-based strategies (Bornilla, 2019). Although educational reforms improved the competency for teaching and learning science from the past years, Filipino learners have continuously failed in scholastic assessments whether national or international.…”
Section: Open Accessmentioning
confidence: 99%
“…Expanding upon the records of literature, attempts have been made to improve science teaching strategies and academic achievement of learners. Many proposals were integrated into school curriculum like adaptation of constructivist view of learning (Garbett, 2011), integration of inquiry-based approach for teaching (Abdi, 2014), ICT integration (Palomares-Ruiz et al, 2020), contextualization or culturebased instruction (Bibon, 2021), and brain-based strategies (Bornilla, 2019). Although educational reforms improved the competency for teaching and learning science from the past years, Filipino learners have continuously failed in scholastic assessments whether national or international.…”
Section: Open Accessmentioning
confidence: 99%
“…Yoon, Miller, and Richman (2020) bring the work to the literature by creating complex systems biology computer-based curriculum for teachers on how to use the online version of the PES and instruction, face-to-face version of the research that is aimed at the same high impact, and as a result, students showed positive perceptions of teacher in biology and roughly equal in both format, it is observed that achieves results. In Bibon's (2022) study, they aimed to develop biological culture-based courses by integrating medicinal plants and technology applications, and as a result, the study shows that the potential of using indigenous medicine as a resource for culture-based courses in biology and technology support is beneficial to this field, participants and users. Wise, Archie, and Laursen (2022) who have experience in instructional practices in the work they have done in the 2-year college biology instructor is to provide a reconnaissance study on the needs and preferences of the technology since, and as a result MCQ biology learning goals outside of inclusive pedagogy and research, such as quantitative skills and a high level of interest and support for technology instructor technology that achieves results, it is observed that design that carries a container of biology.…”
Section: Introductionmentioning
confidence: 99%
“…Most of its land mass is a sovereignty of Municipality of Bacacay connected by a bridge spanning on the narrowest portion of Sula channel (Bacacay, Albay Profile, n.d.). The immersion of Bibon (2021) in the locale revealed the abundance and reliance of its people to folk medicine brought by many shortcomings in the access to quality and modern health care system and facilities. Folk medicine has been the alternative for the majority especially for locals living in the isolated areas of Cagraray.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of buying expensive synthetic medicines, they resort to herbal concoctions and prayer-based therapies as prescribed by their native folk healers. Though accounts were documented on calling folk healers as parabulong referring to a generalist healer, oftentimes they were called as parasantigwar specifically pertaining to the ones performing healing rituals (Bibon, 2021). This culture of traditional healing was subjected to many challenges yet managed to survive compounding the foreign medical system and education brought by American occupation through globalization, and the cruel control of Spanish colonizers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation